From perill to progress:a maternal near miss-secondary postpartum hemorrhage - Ravikumar, Akshitha; Natarajan, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Maternal near miss (MNM) refers to a situation in which a woman nearly dies but survives a life-threatening complication during pregnancy, childbirth, or within the postpartum period. This case report describes the management of a 22-year-old, para 2, living 2 woman who presented with secondary postpartum hemorrhage (PPH) on postoperative day 13, having been transferred from another center. Initial stabilization included broad-spectrum antibiotics and vasopressors. Ultrasound revealed suspected retained products of conception or clots, leading to suction and evacuation, with laparotomy as a contingency. Despite balloon tamponade, ongoing hemorrhage required escalation to peripartum hysterectomy with concurrent bladder rent repair. A multidisciplinary approach involving obstetricians, anaesthetists, and urologists was critical to the successful outcome. The postpartum period was uneventful, and the patient made a full recovery. This case underscores the importance of timely identification, calm decision-making, and coordinated multidisciplinary care in managing MNM scenarios, ultimately saving the patient's life.